Expression and functional analysis of receptor-interacting serine/threonine kinase 2 (RIP2) in Japanese flounder (Paralichthys olivaceus). Issue 75 (April 2018) - Liu, Jinxiang; Cao, Dandan; Liu, Yuezhong; Li, Zan; Si, Yu; Wang, Zhigang; Zhang, Quanqi; Yu, Haiyang; Wang, Xubo
Abstract: Being a key adaptor protein in NOD1/2 and NF-κB signaling pathways, receptor-interacting serine/threonine kinase 2 (RIP2) plays an important role in innate immune response in vertebrates. In this study, we identified and characterized the Paralichthys olivaceus RIP2 gene (PoRIP2). Phylogenetic, alignment, and genomic analysis of PoRIP2 were conducted to determine its conservation and evolutionary relationship with other RIP2 in vertebrates. qRT-PCR results showed that the expression of PoRIP2 was high in the spleen and head kidney. Meanwhile, embryonic development expression profile revealed that it was high in the early developmental stages and hatching stage. In vivo, we examined the expression pattern in different tissues after being challenged with Edwardsiella tarda. PoRIP2 was up-regulated in tissues at different time points. In vitro, the expression of PoRIP2 was also increased after treatment with Poly I:C, PGN, and E. tarda . Transfection and overexpression experiments indicated that PoRIP2 was located in the cytoplasm of the FG-9307 cell line. The pro-inflammatory cytokines, IL-1β, IL-6, and IL-8, could be activated and up-regulated by PGN stimulation in PoRIP2 overexpressed cells. The inhibitory action was obvious in PoRIP2 overexpressed cells, and the quantity of E. tarda decreased. These findings highlight the important role of PoRIP2 in regulating innate immune in P. olivaceus . Our results indicated that PoRIP2 might be involved in immune response and the activation of the NF-κB signaling pathways. Our study can improve the knowledge on the immune system of fish and provide a theoretical basis for the study of prevention and treatment of fish diseases. Highlights: PoRIP2 expressed ubiquitously in all tested tissues and developmental stages. The change of PoRIP2 expression was observed in immune tissues after challenge in vivo and in vitro. Inflammatory cytokines could be induced after PoRIP2 overexpression. E. tarda could be inhibited after PoRIP2 overexpression.